การพัฒนาการจัดการความรู้ด้านการจัดการขยะของเทศบาลตำบลทากาศเหนือ อำเภอแม่ทา จังหวัดลำพูน - อัญชลี ศาลางาม (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The study of The Development of Knowledge Management in Solid Waste Management of Thakadnuae Subdistrict Municipality, Mae Tha District, Lamphun Province aimed to 1) analyze the knowledge management process in solid waste management of Mae Rang Subdistrict Municipality, Pa Sang District, Lamphun Province that received the award for solid waste management 2) analyze the knowledge management process in solid waste management of Thakadnuae Subdistrict Municipality, Mae Tha District, Lamphun Province 3) to find ways to develop the knowledge management in solid waste management of Thakadnuae Subdistrict Municipality. The research was compared the solid waste management between Mae Rang Subdistrict Municipality and Thakadnuae Subdistrict Municipality in analyzing the knowledge management process by using Tuna Model in three main areas as follows; 1) knowledge vision 2) knowledge sharing 3) knowledge asset. The research was a qualitative research. The sample of the study consisted of 11 members that were divided into two groups as follows; the first group was 5 members who concerned in solid waste management of Mae Rang Subdistrict Municipality and the second group was 6 members who involved in solid waste management of Thakadnuae subdistrict Municipality. The sampling method was a purposive sampling and the data were collected by in-depth interview. The research instrument was the semi-structured interview and the data were analyzed by the descriptive statistic. The study was shown as below. The knowledge management process of Mae Rang Subdistrict Municipality was divided into three parts as follows. 1) Knowledge vision ; to reduce the amount of growing garbage in community and create the prototype of zero waste community for distribution at other communities in Mae Rang Subdistrict area. 2) Knowledge sharing; to assign the knowledge sharing techniques of waste management through the village meetings to find ways of reducing waste and garbage incineration. 3) Knowledge asset; there were explicit knowledge such as documents, record, and database to use as a guideline for reducing the amount of garbage in the area. Moreover, there were tacit knowledge such as village philosophers, youth leaders, and learning resources that were used as a guideline for reducing waste in the area and also caused the innovation. The knowledge management process of Thakadnuae Subdistrict Municipality was divided into three parts as follows. 1) Knowledge vision; the villagers knew the segregation of waste before leaving garbage. 2) Knowledge sharing; to manage the village meetings in the area to acknowledge the problem of garbage and participating in the community meetings in each village to find ways of reducing waste. 3) Knowledge asset; there were no explicit knowledge which did not find any documents or database for using as a guideline to reduce waste in the area but it was found that the tacit knowledge was occurred from community leaders in part of transferring knowledge through the public to understand the waste management with the demonstration of waste separation from various color tanks. When comparing the results of analysis of knowledge management process between Mae Rang Subdistrict Municipality and Thakadnuae Subdistrict Municipality, the researcher has offered the approach to develop knowledge management in solid waste management of Thakadnuae Subdistrict Municipality which divided into three parts as follows. 1) Knowledge vision; there should be focused on the potential and the readiness of community to find out the targeting method of waste management in the area together and search for somebody to take responsibility for this work. 2) Knowledge sharing; there should be focused on the participation of community and supporting the activities of knowledge sharing programs. 3) Knowledge asset; storage of information from many activities to make the handbook, creating the prototype community, and taking the result or report of activities to compete in the contest with other organizations.